Students' perceptions of contraceptives in university of ghana. - Nana Nimo Appiah-Agyekum; Esinam Afi Kayi (Tehran University of Medical Sciences, 2013)
Objective: This study sought to explore University of Ghana Business School diploma student's knowledge of contraceptives, types of contraceptives, attitudes towards contraceptive users, preference for contraceptives, benefits, and side-effects of contraceptives. Materials and methods: Data was conducted with three sets of focus group discussions. Participants were systematically sampled from accounting and public administration departments. Results: Findings showed that students had little knowledge of contraceptives. The male and female condoms were the main contraceptive types reported out of the many modern and traditional methods of contraceptives. The main benefits of contraceptives were; ability to protect against STIs, abortions, unwanted pregnancy and psychological trauma. Whilst most respondents preferred future use of pills, side-effects of contraceptives were mostly reported for condoms than other contraceptive methods. Results showed that participants had bad attitudes towards unmarried contraceptive users. Conclusion: Generally, our findings show that detailed knowledge about contraceptives is low. There is a little gap of information on contraception knowledge, timing, and contraceptive types among university diploma students. Reproductive and maternal services should be available and accessible for tertiary students.